Freedom incorporated anticommunism and Philippine independence in the age of decolonization - Woods, Colleen (Cornell University Press, 2020)
"Freedom Incorporated tells the story of American and Filipino anticommunists who sought to turn the Philippines into a laboratory for exportable models of decolonization, postcolonial statehood, and anticommunist warfare"-